REPOSITIONING DIGITAL SOVEREIGNTY AS A CONSTITUTIONAL RIGHT: A CRITIQUE OF THE LIMITATIONS OF PERSONAL DATA PROTECTION IN THE ERA OF ARTIFICIAL INTELLIGENCE - M. Ferdiansyah Kholil (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2026)
The advancement of Artificial Intelligence has transformed the landscape of personal data protection due to the ability of algorithms to generate inferred data and conduct profiling that extends beyond the original purpose of data collection. This situation challenges the effectiveness of data protection regimes that still rely on